Filosofi Tri Hita Karana Dalam Tata Ruang Pura Kereban Langit Di Desa Sading, Badung - Paramadhyaksa, I Nyoman Widya; Swanendri, Ni Made; Witari, Made Ratna (Jurnal Arsitektur Universitas Udayana, 2025)
Keraban Langit Temple is a sacred building complex of Balinese Hindus in Sading Village, Mengwi District, Badung Regency which has a special land character and has various natural and aesthetic site potentials. The site of Pura Keraban Langit is located in a riverbank area with land characteristics that are quite steep, and has a natural cavity in the form of a cave with naturally formed voids in the ceiling. The main prayer room of this temple is in a cave with a void that is directly connected to the sky. In the footprint of the temple also flows water that emerges from a spring that is sanctified by the people in the cave. This water is highly sanctified and becomes a ritual attraction for the devotees who pray in this temple. This brief paper discusses the application of the philosophy of Tri Hita Karana in the spatial and site layout of Pura Keraban Langit. The method applied is a rationalistic study with the focus of the study being the location, site layout, and building layout applicable in Pura Keraban Langit. The results obtained show that in addition to being arranged based on efforts to harmonize the relationship between God, humans, and nature, water flow patterns and temple land characteristics become special guidelines in the design of this temple landscape. Keywords: Pura Keraban Langit, Tri Hita Karana, land, site, natural